Risk factors of caesarean deliveries in urban–rural areas of Bangladesh - Abdulla, Faruq; Hossain, Md. Moyazzem; Rahman, Md. Mahabubur; Rahman, Md. Siddikur; Rahman, Azizur (Frontiers in Reproductive Health, 2023)
Background and Aims The key interest of this researcher is to identify the causes of the ongoing increasing trend of caesarean section or C-section (CS) deliveries in both urban and rural areas of Bangladesh. Methods This study analyzed all the Bangladesh Demographic and Health Survey (BDHS) datasets through Chi-square and z test, and multivariable logistic regression model. Results CS deliveries were found to be more prevalent in urban than rural areas of Bangladesh. Mothers>19 years, mothers>16 years at first birth, overweight, higher education, antenatal care (ANC) visits≥1, whose husbands have secondary/higher education and worker/business, and living in a wealthy family in Dhaka, Khulna, Mymensingh, Rajshahi, and Rangpur divisions had a significantly high likelihood of CS delivery in the urban area. Contrastingly, mothers with ages between 20-39 years, mothers>20 years at first birth, normal/overweight, primary to higher education, business profession, whose husbands are primary to higher educated, ANC visits≥1, and living in a wealthy family in Dhaka, Khulna, Mymensingh, Rajshahi, and Rangpur divisions are more prevalent to have CS delivery in rural areas. The 45-49 years aged mothers have five times higher prevalence of CS (Odds Ratio (OR): 5.39) in urban areas than in rural areas. The richest mothers are more prevalent to have CS in urban areas (OR: 4.84) than in rural areas (OR: 3.67). Conclusion Findings reveal a gradual upward alarming trend in CS with the unequal contribution of significant determinants in urban and rural areas of Bangladesh. Therefore, integrated community-level awareness programs are urgently needed in accordance with the findings on the risks of CS and the benefits of vaginal delivery in Bangladesh.